Multimedia-Based Scout Semaphore Code Learning Mobile Application - Anabella Giuseppe; Michael Tonghayo (Journal of Information System, Technology and Engineering, 2023)
This research aims to analyze how to design a mobile application that can present information about multimedia-based learning that is easy to understand and use for students. The data collection methodology used is a literature study. Making applications based on storyboards, flowcharts, navigation structures, or object diagrams originating from the design stage. All multimedia objects or elements are created and combined into a single application. At this stage, we use software such as Adobe Flash CS4, Adobe Device Central CS4, Adobe Photoshop CS2, and Adobe Audition 1.5. The author provides testing, which was carried out in 2 stages: the first stage was carried out in the emulator environment, and the second stage was applied to the actual device, namely cellphone media. Based on research results, it shows that with a busy level of routine and high mobility, cellphones are a complex and sophisticated technological device, inseparable from everyday life because, apart from being a communication tool, they also have multimedia features that can be used to help implement methods. learning. It becomes easier for users to learn lessons outside of study hours. The use of Flash Lite makes this multimedia-based mobile application more interesting and interactive.